2004
DOI: 10.1002/ana.20320
|View full text |Cite
|
Sign up to set email alerts
|

Fuel utilization in subjects with carnitine palmitoyltransferase 2 gene mutations

Abstract: Patients with the myopathic form of carnitine palmitoyltransferase II (CPT II) deficiency typically experience muscle pain, cramps, and myoglobinuria during prolonged exercise. It has been suggested that carriers of CPT2 gene mutations also may have milder clinical symptoms, but fatty acid oxidation (FAO) has never been investigated in vivo in this group. We studied fuel utilization by indirect calorimetry and stable isotope methodology in four patients with CPT II deficiency, three subjects who carried one CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 28 publications
5
63
0
Order By: Relevance
“…Mutation sites of p.Val368Ile, p.Pro504Leu and p.Val605Leu are located near the acylcarnitine binding sites, though had little effects on K m values. It has been suggested, from correlation studies between genotype and clinical metabolic data, that CPT II gene mutation have a dominant-negative effect on the homotetrameric CPT II protein [Thuillier et al, 2003;Ørngreen et al, 2005]. In the present study, we confirmed this dominantnegative effect of CPT II gene mutations/variations by the kinetic properties of WT and variant CPT IIs (Fig.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mutation sites of p.Val368Ile, p.Pro504Leu and p.Val605Leu are located near the acylcarnitine binding sites, though had little effects on K m values. It has been suggested, from correlation studies between genotype and clinical metabolic data, that CPT II gene mutation have a dominant-negative effect on the homotetrameric CPT II protein [Thuillier et al, 2003;Ørngreen et al, 2005]. In the present study, we confirmed this dominantnegative effect of CPT II gene mutations/variations by the kinetic properties of WT and variant CPT IIs (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies on enzyme activities in fibroblasts of CPT II deficiency patients harboring homozygous and compound heterozygous CPT2 mutations suggest that CPT2 gene mutations exert a dominant-negative effect on tetrameric CPT II [Thuillier et al, 2003;Ørngreen et al, 2005]. To confirm this effect, we examined the kinetic properties of CPT IIs in COS-7 cells singly transfected with: 1) pCMV6-WT, a model of WT, and 2) pCMV6-P504L1 V605L, a model of homozygous variant, and doubly transfected with 3) pCMV6-WT and pCMV6-P504L1V605L at a ratio of 1:1 for each plasmid DNA, a model of compound heterozygous variant.…”
Section: In Vitro Expression and Characterization Of Wtand Variant Cpmentioning
confidence: 99%
“…Such specificity has been reported in myocardiocyte proteomic responses to preconditioning (8). CPT2 deficiency is the most common inborn error of fatty acids oxidation and results in reduced transfer of long-chain fatty acid into mitochondria, and its deficiency compromises the ability to use long-chain fatty acids during exercise (96). To date, 40 point mutations or microrearrangements have been described for the human CPT2 gene (15,124).…”
Section: Discussionmentioning
confidence: 77%
“…However, no reports exist of a correlation between fatty acid oxidation in the muscle and hypercreatininaemia. Interestingly muscle damage has been reported in patients with the myopathic form of CPT2 deficiency, perhaps due to impaired ability to utilise fatty acids [32]. This again does not provide an explanation to the association between TG change and hypercreatininaemia.…”
Section: Discussionmentioning
confidence: 91%